Factors associated with shock in children with dengue hemorrhagic fever - Erick F Kan; T H Rampengan (Indonesian Pediatric Society Publishing House, 2016)
Background Shock in dengue hemorrhagic fever (DHF) still con- stitutes an important problem in children. Predicting DHF patients who will develop shock is difficult. Objective The aim of this study was to find out factors associated with shock in DHF. Methods This was a prospective observational study. Subjects were children hospitalized from April to July 2000 who met the WHO criteria for DHF and had positive serological confirmation. Association between independent variables (age, gender, dura- tion of fever, abdominal pain, vomiting, hepatomegaly, platelet count, hematocrit level, and nutritional status) and the dependent variable (shock) was analyzed by logistic regression model.. Results There were 85 children who met the eligibility criteria consisting of 50 (59%) boys and 35 (41%) girls with an average age of 7.1 years (SD 2.88). Shock occurred in 42 (49%) children. Of the 42 children with shock, the age group of 5-9 years made up the biggest group (57%) consisting of 23 (55%) boys and 19 (45%) girls. Hepatomegaly was found in 32 (76%) children, ab- dominal pain and vomiting in 30 (71%) and 36 (86%) children, respectively, and good nutrition in 22 (52%) children. Shock oc- curred mainly on the fourth and fifth days (76%). Almost half of the patients (45% and 52%) had hematocrit level of 46-50% and platelet count of 20,000-50,000/ml, respectively. By logistic re- gression analysis, it was found that duration of fever, abdominal pain, hematocrit level, and platelet count constituted indepen- dent factors correlating with shock in DHF. Conclusion Abdominal pain, fever lasting four to five days, hema- tocrit level of >46%, and platelet count of <50,000/μl were associ- ated with shock in DHF